2018
DOI: 10.1242/dev.157206
|View full text |Cite
|
Sign up to set email alerts
|

Dusp6 attenuates Ras/MAPK signaling to limit zebrafish heart regeneration

Abstract: Zebrafish regenerate cardiac tissue through proliferation of pre-existing cardiomyocytes and neovascularization. Secreted growth factors such as FGFs, IGF, PDGFs and Neuregulin play essential roles in stimulating cardiomyocyte proliferation. These factors activate the Ras/MAPK pathway, which is tightly controlled by the feedback attenuator Dual specificity phosphatase 6 (Dusp6), an ERK phosphatase. Here, we show that suppressing Dusp6 function enhances cardiac regeneration. Inactivation of Dusp6 by small molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 64 publications
4
78
0
Order By: Relevance
“…27 Missinato et al reported that DUSP6 attenuated Ras/MAPK signalling during regeneration and that suppression of DUSP6 expression could enhance cardiac repair. 28 In our study, CSE exposure up-regulated DUSP6 in HBE cells and lung F I G U R E 5 Overexpression of DUSP6 reverses the inhibition of airway inflammation and fibrosis mediated by HBE cells and lung fibroblasts after TUG1 knockdown. A and B, Expression of DUSP6 was determined in CSE-treated HBE cells and lung fibroblasts transfected with shTUG1 or DUSP6 alone or co-transfected with shTUG1 and DUSP6.…”
Section: Discussionmentioning
confidence: 47%
“…27 Missinato et al reported that DUSP6 attenuated Ras/MAPK signalling during regeneration and that suppression of DUSP6 expression could enhance cardiac repair. 28 In our study, CSE exposure up-regulated DUSP6 in HBE cells and lung F I G U R E 5 Overexpression of DUSP6 reverses the inhibition of airway inflammation and fibrosis mediated by HBE cells and lung fibroblasts after TUG1 knockdown. A and B, Expression of DUSP6 was determined in CSE-treated HBE cells and lung fibroblasts transfected with shTUG1 or DUSP6 alone or co-transfected with shTUG1 and DUSP6.…”
Section: Discussionmentioning
confidence: 47%
“…DUSP6-/-mice with larger hearts was not due to hypertrophy, but rather to hypercellularity of the myocytes. A recent study confirmed a similar finding in the zebrafish heart by suppressing the Dusp6 function, which showed that DUSP6 attenuated Ras/MAPK signaling during regeneration, and inactivation of DUSP6 could enhance cardiac repair [52]. Opposite to the activation of ERK1/2, multiple lines of DUSP6 contained in the mouse heart were specifically generated [48].…”
Section: Targeting Phosphatases and Mapk Scaffold Proteinssupporting
confidence: 53%
“…The preference for AFOG staining may likely be explained by a higher sensitivity for Collagen in particular in zebrafish as suggested by Poss et al [9]. Eight out of the 45 studies [9,29,36,66,73,89,90,94] evaluated the extent of heart regeneration by quantifying the amount of fibrosis on heart tissue sections in 2D where the area of collagen was compared to the total area of the ventricle.…”
Section: Qualitative and Quantitative Analysis Of Cardiac Outgrowthmentioning
confidence: 99%
“…In our systematical analysis we identified a total number of six studies [7,12,49,[87][88][89] that used a functional heart test as a measurement for cardiac recovery after AR. Three of these studies [7,49,89] used electrocardiography (ECG) while the other half [12,87,88] performed echocardiography.…”
Section: Analysis Of Heart Functionmentioning
confidence: 99%
See 1 more Smart Citation